Data Consistency at Digital Traceability: An overview - Julia Kurniasih (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2022)
Digital traceability is the use of electronic records and technology to track the forward movement of a product through various stages of the supply chain and to trace back the product history, including location, transformation, and application. The basis of a traceability system is related to the efficient and precise recording of information. Digital interoperability is an essential component of digital traceability. To increase digital interoperability in Supply Chain Management (SCM), one of which is by meeting the conditions of data consistency running on the interoperability system. Data consistency makes it easy to pool data from multiple sources and allows comparative decision-making. Consistency includes data release formats, classifications, definitions, and taxonomies.